Country inequality rankings and conversion schemes - Carsten Schröder; Timm Bönke (Kiel Institute for the World Economy (IfW), 2012)
Two conversion schemes are usually employed for assessing personal-income inequality from household equivalent incomes: to weight household units by size or by needs. Using data from the Luxembourg Income Study, the authors show the sensitivity of country inequality rankings to conversion schemes and explain the finding by means of inequality decomposition. A bootstrap approach is implemented to test for statistical significance of the results.
Keywords: D31; D63; I32; 330; Inequality; equivalence scale; equivalent income; weighting scheme; decomposition